Designing of imine thiophene-ligated metal-complexes and implication in ethylene polymerization - Shaikh, Maulali H.; Ramekar, V. Rohan; Jawoor, Shailaja; Dash, Soumya R.; Birajadar, Rajkumar S.; Pawal, Sandip B.; Thenmani, Nandakumar; Vanka, Kumar; Chikkali, Samir H. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
Polyethylene is the single largest volume polymer produced globally using Ziegler-type catalysts. Numerous modifications have been reported in search of a better catalyst that can control molecular weight, polydispersity, and branching. In our attempts to identify a suitable imine thiophene-ligated chromium complex, we examined 9 different titanium complexes computationally. The DFT investigations considered barriers for insertion, propagation, and termination by beta-H elimination or chain transfer, and identified N-(4-methoxyphenyl)-2-phenyl-1-(thiophen-2-yl)ethan-1-imine(L9) as the most suitable ligand. Subsequently, L9 was prepared in good yield (70%) by condensing 2-phenyl-1-(thiophen-2-yl)ethan-1-one with 4-methoxyaniline. Ligand L9 was treated with early transition metal precursors (Ti, Cr, Zr) to generate a homogenous catalyst. The identity of these catalysts was unambiguously ascertained using a combination of NMR, ICP, FT-IR, UV-Vis spectroscopy, and ESI-MS. The performance of L9-ligated titanium complex [Cat.1] was examined in ethylene polymerization using MMAO as a co-catalyst. Insertion of ethylene was tracked using high-pressure NMR experiments and Cat.1 was found to be active in the polymerization. Ethylene polymerization conditions were optimized to obtain high activity and molecular weight polyethylene. The chromium complex [Cat.2] outperformed the Ti and Zr-derived catalysts with the highest TOF of 6294 mol of PE/mol of Cr/h. Cat.2 produced high molecular weight, high-density polyethylene.
Keywords: Cr-complexes; DFT; high-density polyethylene; Imine thiophene ligand; Polyethylene